Analysis and Optimization of Warehouse Sustainability Using the Sustainable Value Stream Mapping (SUS-VSM) Method at PT XYZ - Friska Aryanti; Farida Pulansari; Isna Nugraha (EPI International Journal of Engineering, 2025)
Warehouse operations are a critical component of the supply chain system as they manage material flow before entering the production process. The Central Warehouse handles high-volume material operations, requiring an efficient and sustainable warehousing system to support Environmental, Social, and Governance (ESG) targets and the Net Zero Emission 2060 initiative. This study aims to analyze and optimize sustainable warehouse processes using the Sustainable Value Stream Mapping (SUS-VSM) method integrated with RFID technology. The research methodology includes mapping the current state of SUS-VSM, classifying activities into value-added (VA), necessary non-value-added (NNVA), and non-value-added (NVA), waste analysis, root cause identification using the Five-Whys method, and designing the future state of SUS-VSM. The results indicate that the total lead time of the warehouse process is 4,516.31 minutes, with a value-added time of 36.59 minutes and a Process Cycle Efficiency (PCE) of 0.81%. The dominant wastes identified include waiting, transportation, motion, inventory, and overprocessing, which are caused by the lack of system integration, reliance on physical documents, and manual verification processes. Proposed improvements such as the implementation of RFID, a Warehouse Management System (WMS), document digitalization, and material flow optimization reduce lead time to 4,395.19 minutes and increase PCE to 0.83%, while also improving sustainability indicators including waste efficiency, energy process, safety, and time efficiency. The findings demonstrate that the implementation of RFID-based SUS-VSM enhances warehouse operational efficiency while supporting sustainable warehousing systems.